Strengthening resources through identity-reframing interventions: empowerment for students with low socioeconomic status and with ADHD symptoms - Möller, Julius; Reiss, Stefan; Jonas, Eva (Frontiers in Psychology, 2025)
IntroductionStudents draw on multiple resources to pursue a higher education degree. Vulnerable student groups, such as those from low socioeconomic status (SES) or with symptoms of Attention Deficit Hyperactivity Disorder (ADHD), may have fewer resources at their disposal. An essential resource in higher education settings is social belonging among their peers within the academic environment. Students from low SES or with ADHD symptoms might lack this sense of belonging due to their different background or their additional needs.MethodsBased on the social cure approach, we investigate two identity-reframing interventions (N = 392) that foster social belonging (Study 1) and relatedness need satisfaction (Study 2) and support academic engagement through reframing deficit narratives.ResultsIn Study 1, we found that the identity-reframing intervention successfully buffers the negative effect of low SES on social belonging, which in turn is linked to a higher academic self-concept and reduced fear of errors. In Study 2, the identity-reframing intervention mitigated the detrimental effect of ADHD symptoms on relatedness satisfaction. Further, we found that the intervention reduces the effect of ADHD symptoms on intrinsic motivation via academic identity.DiscussionWe discuss how identity-reframing interventions foster social belonging and, in the context of social cure, positively influence academic engagement. The findings suggest that support programs for vulnerable student groups could be more effective if they emphasize the strengths gained from contending with past challenges, transforming these into valuable resources in higher education.